The role of vernacular typography in the linguistic landscape of multicultural Singapore: a multimodal analysis case study of a gentrified street - Yam, Angeline Min-Yee (2024)
The art of typography has been receiving a fair amount of attention at the crossroads of linguistic landscape, garnering the interest of sociolinguistics. Technological advancement has pushed typography to the forefront alongside traditional modes of communication. It is therefore no longer viable to limit the analysis of communication modes to just speech and writing but to also consider typography as an important semiotic mode for meaning potential in its own right. This paper attempts to present a case study of analysing the vernacular typography of a gentrified street (Haji Lane) in Singapore through a multimodal analysis approach. The results provided preliminary insights into how Singaporeans through the creative expression of typography and language use, assert their 21st-century multicultural identity alongside the nation's de facto language – English, in a situated gentrified urban environment. The study also contributes to an on-going endeavour of semiotizing typography as a mode for rational explanation.